Solat bio theraphy module / Noor Azura Zainuddin ... [et al.] - Zainuddin, Noor Azura; Aurani, Jamalia; Rosmani, Arifah Fasha; Wan Daud, Wan Naimah; Md Dali, Hamlussalam (Universiti Teknologi MARA, Perlis, 2014)
This module is developed to give an explanation to Muslims about effective techniques as a complementary treatment and prevention for physical, mental and spiritual illness. The module also focuses on the quality of worship to Allah by adapting integrated techniques in religion and science to improve the level of humility in prayer. The methodology of this module is based on library research